Pengaruh Tanggung Jawab Kerja Terhadap Kinerja Karyawan Di Ramada By Wyndham Bali - Putra, Putu Bayu Surya Dharma; Pangarso, Astadi (eProceedings of Management, 2024)
The COVID-19 pandemic has increased competition among hotels. Organizations are forced to balance staffinglevels to retain their workers in the face of diminishing performance and growing responsibilities. Businesses thatdon't compete will eventually disappear from their sector. As such, it is imperative that businesses maintain andenhance their performance on a constant basis. This study looks at how job responsibility affects Ramadaemployees' performance. Written by Wyndham Bali. Using surveys and questionnaires, this research employs aquantitative methodology to collect primary data from 91 respondents and analyze it using simple linear regression.Based on hypothesis testing, the research results indicate that work responsibility has a significant impact onperformance. The theoretical contribution of this study expands our understanding of the specific impact of jobresponsibility on performance at Ramada By Wyndham after the COVID-19 pandemic. SPSS version 25 wasemployed as the data analysis program. The findings of the study show that work responsibility has a major impacton Ramada By Wyndham employees' performance. According to data analysis, work responsibility (X) influencesperformance (Y) by 33%, with other factors not included in this study accounting for the other 67% of the variation. Recommendations to optimize the responsibility processes are derived from the findings of the hypothesis testing.This makes it easier for the business to evaluate its own performance requirements and provides information foranalyzing employee performance inside the company. Keywords-work motivation, work environment, and employee performance